PENERAPAN PEMBELAJARAN BERBASIS MASALAH DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Siregar, Nur Fauziah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
This study aims to determine: (1) to increase mathematical problem solving ability of students through the application of problem-based learning, and (2) to increase active activity levels of students with problem-based learning. This type of research is a class action. Subjects in this study are students of cass VII-3 SMP Negeri 7 Padangsidimpuan. The instrument uses a form of problem-solving ability test descriptions and observation. The results show that in the first cycle has not show optimal results therefore it needs the second cycle. In the second cycle shows an increase in the problems solving ability of students. In the first cycle is 50% rising to 89% in the second cycle. The levers of active student’s activity based on the observation shows at each meeting including both categories. Based on these result, the researcher suggests that the problem-based learning can be an altervative for teachers of mathematics to be developed as one of the effective learning to improve students’ mathematics problem solving ability and increasing the activity of active students.